Valuing the environment in developing countries: Modeling the impact of distrust in public authorities' ability to deliver public services on the citizens' willingness to pay for improved environmental quality - Birol, Ekin; Das, Sukanya (International Food Policy Research Institute, 2010)
In this paper, we employ the choice experiment method to estimate local citizens' valuation of a public intervention that proposes to improve the quality of an important environmental resource, namely, the Ganges River in India. To elicit citizens' willingness to pay (WTP) higher municipality taxes for an intervention that proposes to improve the quantity and quality of wastewater treated by the local sewage treatment plant (STP), 150 randomly selected citizens of the municipality of Chandernagore, located on the banks of the Ganges River in West Bengal, were interviewed. The findings reveal that almost all (98 percent) of the citizens value the quality of the water and the environment in the Ganges, though a great majority (90 percent) protested the intervention by not choosing the improved STP scenario in at least one of the eight hypothetical markets in which they were asked to participate. When asked their reasons for not preferring the improved scenarios, 92 percent of them stated that they do not trust the authorities to efficiently and effectively manage the funds generated through additional taxes. The protest responses were controlled for with the use of the nested logit model (NLM). The results reveal that the citizens are willing to pay significant amounts to ensure that the intervention takes place and that an improved STP treats larger amounts of wastewater to a higher quality before discharging it to the Ganges. Therefore, to improve the wastewater management services and the related environmental quality in the water bodies into which treated wastewater is deposited, the municipalities could rely—at least to some extent—on their citizens' WTP higher taxes for provision of improved services. To capture this WTP, however, municipalities' performance, trustworthiness, and accountability, as well as the citizens' perceptions of these, should be improved.